Sistem Pakar Diagnosa Penyakit Ganguan Kehamilan Menggunakan Metode Berbasis WEB - Ismail Ismail; Asni Asni; Sagenawati Sagenawati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Regnancy is a physiological stage that requires intensive monitoring and attention because various complications can arise and potentially threaten the safety of the mother and fetus. The limited number of medical personnel and the low level of health literacy of pregnant women regarding the symptoms of pregnancy disorders are often factors causing delays in the diagnosis and early treatment process. Therefore, this study proposes the design of a web-based expert system that functions as an aid in diagnosing pregnancy disorders by applying the Certainty Factor (CF) method. The Certainty Factor method was chosen because it is able to represent the level of expert confidence in a hypothesis based on symptoms provided by the user, thus resulting in more measured decisions. The system was developed using the PHP programming language with MySQL database support, and is designed to be accessible online through a web-based interface. Test results show that the system has a fairly high level of accuracy, with the diagnosis concordance rate reaching approximately 90% with the expert.